GEODIVERSITY AUDIT AND ACTION PLAN FOR UPPER CATCHMENT AREA OF GERSA RIVER (RODNEI MOUNTAINS, BISTRIȚA-NĂSĂUD COUNTY, ROMANIA) - Bâca, Ioan (REVISTA GEOGRÁFICA ACADÊMICA, 2015)
Geodiversity Audit is an inventory and assessment process, wich represents the basis for elaborating the Geoconservation Action Plan. The geodiversity includes the abiotic factors (rocks, minerals, soils, landforms) that sustain the life on the Earth, and owns economic, social, environmental, tourist and educational functions. This study proposes an audit of geodiversity from Gersa catcment area and an Action Plan for future planning and tourist valorization projects by local and county authorities. Gersa Valley is a geomorphological subunit located in the southern part of Rodnei Mountains (Bistrița-Năsăud County) and contains in the superior sector some landforms with high degree of attractiveness, such as Izvorul Tăușoarelor Cave, Izvorul Calului Gorge and Bârlea Massif. By their configuration these landforms has a great potential for engaging in scientific and recreational activities (caving, hiking, gorge walking, canyoning, mountain biking). Keywords: geodiversity, geologic heritage, geoconservation, geosite, action plan, Rodnei Mountains, Gersa River, Izvorul Tăușoarelor Cave, speotourism, activ leisure